Perbandingan Karakter Cinta Tanah Air dan Cinta Damai dalam Pembelajaran IPS - Dila Yathasya; Romadonia, Marisa; Ningsih, Ismiarti; Zulkhi, Muhammad Dewa (Cahaya Ilmu Cendekia Publisher, 2022)
Purpose of this Research: The purpose of this study was to compare the character of love for the homeland and the character of peace in social studies learning Research Methods: In this article, the author takes the title of the comparison between the character of love for the homeland and love of peace in social studies learning. That way, the hypothesis that the author compiles is 'The character of love for the homeland is higher than the character of peace-loving in learning social studies subjects. To test this, the authors conducted research with several social studies in schools. And also, to do the proof, the author conducted a statistical T-test. Main Findings: The result is that each variable of the character of love for the homeland and the character of peace-loving has a significant comparison, with a value of sig < 0.05, and in each dominant variable in the good category. Novelty of this Research: The novelty of the research compares the character of love for the homeland and the character of peace-loving. This study is to describe the comparison of religious and peace-loving characters.